Impact of sowing methods and weed control practices on yield and economics of wet direct seeded rice - Satapathy, B S; Duary, B; Saha, Sanjoy; Munda, S; Chatterjee, D (ORYZA-An International Journal of Rice, 2021)
Wet direct seeding is proved as a viable alternate to conventional transplanting method of rice. Maintenance of optimum population by adopting an appropriate sowing method followed by judicious weed control practices ensures profitability of wet direct seeded rice (W-DSR). A field experiment was carried out to find out a suitable sowing technique and weed control options for enhancing productivity and economics of W-DSR. The W-DSR was infested with twelve numbers of weed species comprising of eight families under different sowing methods. The composition of sedges, broadleaved (BLW) and grassy weeds was 83.07, 11.0 and 5.93%, respectively. Irrespective of sowing methods, weeds such as, Echinochloa glabrescens and Leptochloa chinensis among grasses, Cyperus difformis and Scirpus juncoides among sedges and Lindernia anagallis among BLW were dominant. Drum seeding recorded 6.9 and 12.7% higher gross and net return, respectively than broadcasting, but it was at par with spot seeding. Highest B: C ratio of 2.07 was recorded with drum seeding, whereas spot seeding recorded lowest B: C ratio (1.99). Crop-weed competition caused 31.7% reduction in grain yield with W-DSR. Application of early post-emergent herbicide bensulfuron-methyl + pretilachlor @ 60+600 g/ha at 10 DAS, azimsulfuron @ 35 g/ha at 20 DAS, and bispyribac sodium @ 30 g/ha at 20 DAS recorded increase in grain yield 40.3, 40.1 and 39.8%, respectively over the weedy check. Ready mix bensulfuron-methyl + pretilachlor @ 60+600 g/ha at 10 DAS registered highest B: C ratio (2.16) but it did not vary significantly with bispyribacsodium @ 30 g/ha and azimsulfuron @ 35 g/ha.